Az egyházi könnyűzene fogadtatása és megítélése a szocialista Magyarországon - Povedák Kinga; Vallás, egyén, társadalom (2013) (Szeged) (2014)
This paper investigates the debates that characterized the past decades since popular religious music appeared in Hungarian church music scene. The new style has been a topic of great controversy in various ways since its beginnings. By many it is considered the most effective instrument for spreading Christianity among younger generations. However, many opponents dislike the entering of this modern church music rooted in popular culture into the realm of Christianity. My paper focuses on the conflicts that reveal the differences between the „traditional” and „modern” contemporary vernacular Chirstianity at once.
Keywords: Bölcsészettudományok; Filozófia, etika és vallástudományok; Művészetek (művészetek, művészettörténet, előadóművészetek, zene)